Assessment of the Benefits and Challenges of Digital Braille Assistive Devices in Promoting Inclusivity of Learners with Visual Impairment in Kenya - Gikandi, Joyce; Kimaru, Serah; Mwangi, Judy; Mugwe, Mary (Acitya: Journal of Teaching and Education, 2025)
This study focuses on assessment of the benefits and challenges of digital braille assistive devices in relation to their relevance in promoting inclusivity of learners with visual impairment (VI) in special and integrated education. The study was guided by universal design for learning and assistive technology theories. The study adopted a descriptive survey design within a mixed methodology approach. The study was restricted within 2 institutions in Kenya: a private University (mainstream) and a special school for the blind. The two key study objectives were to assess the benefits of digital assistive devices for the learners with VI in relation to promoting inclusivity in education. Secondly, the study examined the challenges learners face in using these devices in special and mainstream education. The findings show that using digital braille assistive devices for visually impaired learners offer significant benefits. The key benefits include promoting educational access, learner’s independence and enhancing learning opportunities. However, several barriers remain inadequately addressed. Barriers include adequate device access, device maintenance/repair delays, limited training, and inadequate support systems. The study underscores the importance of increasing device availability, improving maintenance and support, and adequate training for both learners and educators. Despite the challenges, the devices' potential to improve inclusivity and foster independence is evident. The study recommends that the government should develop and implement a national policy that ensures adequate availability of digital braille assistive devices. Schools should establish robust policy and support systems for use of assistive technologies, and regular training for both students and educators.